2007
DOI: 10.3322/canjclin.57.1.30
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Estimating United States and State-level Cancer Incidence Counts for the Current Calendar Year

Abstract: The American Cancer Society (ACS) has published the estimated number of new cancer cases and deaths in the current year for the United States that are commonly used by cancer control planners and the media. The methods used to produce these estimates have changed over the years as data (incidence) and statistical models improved. In this paper we present a new method that uses statistical models of cancer incidence that incorporate potential predictors of spatial and temporal variation of cancer occurrence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 11 publications
4
86
0
2
Order By: Relevance
“…The findings are also in agreement with other researchers (Demers et al, 1992;Pickle et al, 2007) who found that longer survival time is a negative predictor of agreement between DC data and SEER registry incidence data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings are also in agreement with other researchers (Demers et al, 1992;Pickle et al, 2007) who found that longer survival time is a negative predictor of agreement between DC data and SEER registry incidence data.…”
Section: Discussionsupporting
confidence: 93%
“…In a study of cancer incidence among radiologic technologists during 1983 to 1998, Sigurdson et al (2003) For almost 50 years, the American Cancer Society (ACS) has used DC data as part of its formula for estimating cancer incidence, and periodic reviews have deemed the results useful and reliable (Silverberg & Lubera 1983). Describing the new method of estimating cancer incidence adopted by ACS, Pickle et al (2007) criticized the use of mortality information for its weak link to incidence in cancers with better survival rates. Burlington, Iowa.…”
Section: Mortality Data and Cancer Identificationmentioning
confidence: 99%
“…Since the American Cancer Society (ACS) began producing estimates of new cancer cases in the current year, the method has been refined several times to take advantage of improvements in data and statistical methods. Beginning with 2007, we are using a new projection method described by Pickle et al 12 in an accompanying article in this issue of CA. The new method is a spatiotemporal model based on incidence data from 1995 through 2003 from 41 states that met NAACCR's high-quality data standard for incidence, covering about 86% of the US population.…”
Section: Estimated New Cancer Casesmentioning
confidence: 99%
“…15 Chondrosarcoma, the second most common malignant bone spine tumor, is more prevalent in males (2:1) with a higher incidence in middle-aged adults. 16 Despite the fact that most chondrosarcomas are low to intermediate grade, their locally invasive character usually results in high recurrence rates and death due to recurrent or progressive disease unless aggressive surgical treatment is pursued.…”
Section: Discussionmentioning
confidence: 99%